Strategi Pengembangan Bisnis PT Bogor Kopi Indonesia di Kabupaten Bogor, Jawa Barat - Doni Sahat Tua Manalu; Suharno Suharno; Widya Hasian Situmeang; Ferdisar Adrian; Veralianta br Sebayang; Ade Astri Muliasari (Journal of Integrated Agribusiness, 2023)
PT Bogor Kopi Indonesia is a company engaged in the field of coffee marketing and coaching for coffee farmers in the Bogor Regency area. Currently, the consumption rate of coffee and its derivative products is increasing, causing the demand for coffee agricultural products to also increase. This encourages the coffee industry for upscaling their strategy to capture these opportunities. The purpose of this research is to find out the exact strategy for PT Bogor Kopi Indonesia to develop their. This study uses the IFE and EFE matrices as identification tools related to the company's internal and external factors, the IE matrix indicate the position of the business strategy, and uses SWOT analysis to determine what strategy the company will run. The results obtained show that PT Bogor Kopi Indonesia is in a hold and maintain position with a weighted average IFE of 2.6 and EFE of 2.7. Based on the results of the study, the strategy used is market development in the form of digital marketing applications as a form of PT Bogor Kopi Indonesia's marketing channel. This application is also a form of company adaptation to the current digitalization era. Through this strategy, it is hoped that the market for the company's products will have a wider reach and be increasingly recognized by the public so that the branding of Bogor Kopi Indonesia will also be increasingly recognized by the public.